2004
DOI: 10.1016/j.jasms.2003.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of amidinated peptide ions

Abstract: The collision-induced dissociation characteristics of amidinated and unmodified tryptic peptides are compared using an ion trap mass spectrometer with both electrospray ionization and matrix-assisted laser/desorption ionization (MALDI). Several fragmentation pathways in a number of tryptic peptides of various precursor charge states are found to be enhanced. The additional information conveyed by the observed fragment ions should facilitate protein identifications. (J Am Soc Mass Spectrom 2004, 15, 158Ϫ167)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 36 publications
(69 reference statements)
0
54
0
Order By: Relevance
“…The samples were allowed to air-dry at room temperature and were then inserted into the mass spectrometer and subjected to MALDI-MS analysis. Prior to analysis, the mass spectrometer was externally calibrated with a mixture of Angiotensin I, Glu-fibrino-peptide B, ACTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and ACTH . For MS/MS experiments, the instrument was externally calibrated with fragments of Glu-fibrino-peptide.…”
Section: Matrix-assisted Laser Desorption/ionization Tof/ Tof Mass Spmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were allowed to air-dry at room temperature and were then inserted into the mass spectrometer and subjected to MALDI-MS analysis. Prior to analysis, the mass spectrometer was externally calibrated with a mixture of Angiotensin I, Glu-fibrino-peptide B, ACTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and ACTH . For MS/MS experiments, the instrument was externally calibrated with fragments of Glu-fibrino-peptide.…”
Section: Matrix-assisted Laser Desorption/ionization Tof/ Tof Mass Spmentioning
confidence: 99%
“…This modification induces selective dissociation of Nterminal peptide bonds in gas phase fragmentation experiments, enabling the facile identification of N-terminal residues. More recently, Beardsley and Reilly [16] illustrated that the use of the N-terminal residue of a peptide as a search constraint reduced the number of candidates extracted from a sequence database and improved database-matching techniques by reducing the occurrence of false-positive assignments. In their study, free amino groups were selectively modified with an amidine label, a form of labeling that has also been employed as a tag in comparative proteomics [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bergquist and co-workers [114] obtained very large deviations from the expected ratios when using LC-FTICR-MS. In a recent paper, the effect of this amidination procedure on peptide fragmentation patterns was also examined [115].…”
Section: Tagging Methods Specific For Other Amino Acidsmentioning
confidence: 99%
“…Beardsley and Reilly and coworkers reported that peptide bond of the Nterminal amino acid of an amidinated peptide is preferentially dissociated in the MS/MS process, and, therefore, b 1 and y n-1 ions are the most abundant among fragment ions [35,36]. In the case of a picolinamidinated tryptic peptide like AENDVGDK, where the C-terminal lysine residue is picolinamidinated, all of the y-series ions should have a picolinamidination tag at the C-terminal and thus would yield a strong signal.…”
Section: Sequencing Picolinamidinated Tryptic Peptide By Ms/msmentioning
confidence: 99%